Pliocene summer sea surface temperature reconstruction using silicoflagellates from Southern Ocean ODP Site 1165 - Whitehead, JM; Bohaty, SM (2003)
In the modern marine environment the silicoflagellate genus Dictyocha is rare, or absent, south of the Antarctic polar front (APF); the genus Distephanus, in contrast, is dominant. In sediments recovered from ODP Site 1165, 1600 km south of the front,however, three intervals where Dictyocha is abundant are interpreted to represent Pliocene warm events. Comparison of our data with Ciesielski and Weaver's [1974] modern core top silicoflagellate relationship with sea surface temperature (SST) indicates that at Site 1165 mean annual SST was approximately 5°C at 3.7 Ma (event 1), and approximately 4°C at 4.3-4.4 Ma (event II) and 4.55-4.8 Ma (event III). Event I represents a 5.5°C warning, and events II and III represents a 4.5°C warming relative to modern mean annual SST. Dictyocha is absent from other Site 1165 Pliocene intervals, which suggests that cooler SST (<2°C) prevailed. The warm events detected at Site 1165 may represent times when North Atlantic Deep Water production and ocean heat transport into the Southern Ocean exerted maximum influence.